A new species of the genus Vellozia (Velloziaceae) from Minas Gerais, Brazil, with comments on endemism, distribution and conservation - Alves, Ruy José Válka; Sadala-Castilho, Rachel; Lima, Heloísa Alves De; Guimarães, Alessandra Ribeiro; Wetzel, Maria Luíza Ribeiro; Silva, Nílber Gonçalves Da (Phytotaxa, 2017)
Vellozia fontellana is described as a new species from the Ibitipoca massif in Minas Gerais, Brazil. This heliophilous species has sometimes been identified as V. crinita in herbaria and recent literature, but is readily distinguished by morphology, anatomy and occurrence restricted to northward slopes exposed to full sun exposure. The original description of V. crinita, translated from Latin, is complemented by information gathered from our collections and observations in the type locality spanning the last three decades of field work.